HAKIKAT PERKEMBANGAN DALAM KONSELING - Ulfiah Ulfiah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2009)
Development is a set continuous progressive changes, systematic and accumulative. Progressive means that changes have a forward orientation, while systematic and continuous mean that all development’s stage are related and cannot be separated from other phases. Traditionally human life development can be considered as a curved line, where those process generated very fast in prenatal, infant, and adolescence. This curved line would then step onto plateau which describes a stabil condition in adulthood and degrades when people aged. Developmental point of view in councelling—in this case—were focused on individuals potential development including intellectual aspect, affective, social, emotional and religiousity aspect—thus, those individual will develop themselves to a higher level of development.